2004
DOI: 10.1055/s-2004-834892
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of 3,4-Dihydro-2H-pyrido[1,2-a][1,3,5]triazin-2-one Derivatives fromN-(2′-Pyridinyl)benzoylacetamide and Nitrosobenzenes

Abstract: S y n t h e s i s o f 3 , 4 -D i h y d r o -2 H -p y r i d o [ 1 , 2 -a ] [ 1 , 3 , 5 ] t r i a z i n -2 -o n e sAbstract: A convenient method leading to fused pyrido[1,2-a] [1,3,5]triazine-2-ones is described. It consists in a one-pot, two-step reaction of N-(2¢-pyridinyl)benzoylacetamide with nitrosobenzenes. On the other hand, N-(2¢-pyridinyl)acetoacetamide provides a C-2 condensation/addition product with nitrosobenzene. N-(2¢-Pyridinyl)benzoylthioacetamide and N-(2¢-pyridinyl)acetothioacetamide with nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Zaleska et al reported the synthesis of fused pyrido[1,2‐ a ][1,3,5]triazin‐2‐one derivatives 450 by the reaction of 433 and two equivalent of nitrosoarenes 449 [195]. The reaction may be initialized from the C2‐addition/condensation between β ‐keto amides and the nitrosoarenes.…”
Section: Six‐membered Heterocycles With Multiple Heteroatomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zaleska et al reported the synthesis of fused pyrido[1,2‐ a ][1,3,5]triazin‐2‐one derivatives 450 by the reaction of 433 and two equivalent of nitrosoarenes 449 [195]. The reaction may be initialized from the C2‐addition/condensation between β ‐keto amides and the nitrosoarenes.…”
Section: Six‐membered Heterocycles With Multiple Heteroatomsmentioning
confidence: 99%
“…The β-keto amide intermediate 447 was prepared by heating equimolar amounts of anthranilic acid 445 with 2,2,6-trimethyl-4H-l,3-dioxin-4-one 446 in xylene while distilling off acetone (Scheme 111) [194]. 3,5]triazin-2-one derivatives 450 by the reaction of 433 and two equivalent of nitrosoarenes 449 [195]. The reaction may be initialized from the C2-addition/condensation between β-keto amides and the nitrosoarenes.…”
Section: Six-membered Heterocycles With Multiple Heteroatomsmentioning
confidence: 99%
“…In the reactions of ethyl acetoacetate and variously substituted 2-aminopyridines, we obtained the corresponding pyridilides 4a-d (4d had not previously been reported), which were then treated with nitrosobenzene in methanol in an attempt to obtain C-2 disubstituted products of type 3. 6 Using two equivalents of nitrosobenzene yielded unexpected products; the spectra and elemental analyses encouraged the conclusion that the actual products were nitrones 5a-e (Scheme 1).…”
mentioning
confidence: 97%
“…It should be noted that the introduction of a phenyl group in place of the methyl group at C3 of 4a totally changes the reactivity of the corresponding pyridylide against nitrosobenzenes. 6 The presence of several nucleophilic centres in a-amidoa-aminonitrones 5 allowed their use in dialkylation reactions with alkyl dihalides. First we examined the reaction with diiodomethane in anhydrous DMF.…”
mentioning
confidence: 99%
“…HPBA was prepared with 2-aminopyridine and ethyl benzoylacetate in xylene according to a previously reported procedure. 17 1 and 2 were synthesised and crystallised via slow diffusion of Ln(NO 3 ) 3 Á6H 2 O, HPBA and NaOH in MeOH. X-ray crystallographic analysis revealed unexpected dinuclear structures bridged by two PBA À ligands, which are quite different molecular structures reported in ref.…”
mentioning
confidence: 99%